Ornamented lives - Valsiner, Jaan (Advances in cultural psychology., 2019)
Ornamented Lives is a theoretical synthesis of cultural psychology, aesthetics, and philosophy of meaning construction. It is an extension of the author's theory of Semiotic Dynamics (Culture in Minds and Societies, 2007) to the field of ornaments. Ornaments are not merely "decorations" but play the important role of guiding the affective depths of the human minds. This is done by capturing the whole fields of perceivable peripheral spaces and filling them with highly recursive forms. The book concentrates on the visual ornaments of various kinds, indicating in them the tensions between basic forms--linear and curvilinear. This tension is present in human construction of environments--natural growth involves curvilinear forms while human constructions introduce linearity. The basic tension between linear and curvilinear infinities is expressed in the use of spiral forms in art and architecture. The book builds a theoretical account of human beings constantly creating sublime life occasions that give them affective charge for dramatizations of ordinary living. Episodically the sublime acquires new quality--becomes aesthetic. The coverage in this book links the aesthetic, the sublime, and the mundane into one theoretical scheme within cultural psychology.